Cognition : - Reisberg, Daniel (W.W. Norton & Co., 2013)
Cognition uses the best of current research to help students think like psychologists and understand how cognitive psychology is relevant to their lives. The Fifth Edition offers a streamlined presentation, introduces an attractive new full-color design and an expanded art program, and has been thoughtfully updated with the best of current research.